Ghrelin: A novel peptide with therapeutic effect in certain cancers? - Aydin, Suleyman; Geckil, Hikmet; Karaoglu, Aziz; Elkiran, Emin Tamer (Churchill Livingstone, 2007)
[Abstract Not Available]
Keywords: In-Vitro